Heat Transfer by Natural Convection through V-Corrugated Plates - Ali, Mohammad; Hasanuzzaman, M (Journal of Mechanical Engineering, 2008)
An experimental investigation is performed on natural convection heat transfer through a square enclosure of V-corrugated vertical plates. The objective of this investigation is to study the variation of heat transfer rate through the square enclosure with the variation of both hot and cold plate temperatures. Hot plate temperature is varied by heat input. To vary cold plate temperature two parameters are considered: one is mass flow rate of water used to remove heat from cold plate and the other is the inlet temperature of water. Air is the media to transfer heat from the hot V-corrugated plate to cold V-corrugated plate. The result shows that the increase of mass flow rate increases the heat transfer rate and the decrease of water inlet temperature increases the heat transfer rate. Journal of Mechanical Engineering Vol.36 Dec. 2006 pp.1-5 DOI = 10.3329/jme.v36i0.804